Design and optimisation of direct-driven PM variable-flux synchronous generators for directly grid-connected slip-synchronous wind-turbines - Amuhaya, Lilian Livutse (Stellenbosch : Stellenbosch University, 2017)
Thesis (PhD)--Stellenbosch University, 2017.